Partitioning nutrients cycling in a constructed subsurface wetland treating piggery wastewater for pollution control - Udom, I. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Piggery wastewater management is an environmental concern due to the risk of nutrient pollution on surface and groundwaters. In surface and subsurface flow constructed wetlands, nutrient removal show inconsistency, and the contributions of their various partitions remain unclear; making the optimization of Constructed Wetlands (CW) systems difficult. Pennisetum clandestinum plants and sediment in constructed wetlands play important roles in nutrient polishing and reduction but their capacities have not been partitioned. An experimental constructed Horizontal Sub-Surface Flow Wetland (HSSFW) planted with Pennisetum clandestinum was fed from a piggery wastewater source at Akwa Ibom State University (AKSU). Samples of piggery wastewater were collected before and after each six respective days of detention in the wetlands. Nutrient mass balances and effluent qualities of the partitions were evaluated based on World Health Organization (WHO) and Nigeria Environmental Standards Regulation Enforcement Agency (NESREA) benchmarks. Nitrogen detention by sediment, plant uptake, denitrification and water column partitions in planted HSSFCW varied between 4.32-18.3, 8.71- 40.3, 6.6-17.4 and 24-80.37% respectively, while the unplanted HSSFCW nitrogen detention varied between 5.3-24.3, 6.3-16, 59.7- 88.4% respectively. Phosphorus detention in planted HSSFCW varied between 7.2-45.2, 3.5-28.6 and 26.2-89.3% for sediment, plant and water column concentrations respectively, while the unplanted HSSFCW phosphorus equilibrium between sediment and water column fluctuated between 9.8-55.6% and 44.4-90.2% respectively. NESREA benchmarks was generally attained in three days. The result outlined the importance of plant uptake and sediment storage as major nutrient removal pathways in wastewater polishing and improving pollution control. Increasing the proficiency of these compartments would also improve removal efficiency and reduce nutrient impact on land and water.